2019
DOI: 10.12659/msm.911799
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Method to Measure Skin Thickness in Leg Edema in Pregnant Women Using B-Scan Portable Ultrasonography: A Comparison Between Obese and Non-Obese Women

Abstract: BackgroundThis study aimed to use a portable ultrasound method to quantitatively measure skin thickness and to compare leg edema in obese and non-obese pregnant women.Material/MethodsThirty-six pregnant women (17 primiparas and 19 multiparas) at 27/28 and 37/38 weeks of pregnancy, with and without leg edema, had their lower leg skin thickness measured using a B-scan portable ultrasonography device (72 legs and maximum of 98 measurements). Measurements were compared between women who were obese prior to pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 22 publications
1
27
0
6
Order By: Relevance
“…However, the quantification of extravascular fluid overload via ultrasound has rarely been studied in adults and never previously attempted in infants with CHD ( 26 , 35 ). Yanagisawa et al used ultrasound to evaluate for skin edema in pregnant women and was able to manually measure the depth of subcutaneous edema ( 26 ). A study by Eisenbeiss et al demonstrated that subcutaneous tissue thickness increased following fluid infusion and can be measured by ultrasound in healthy adult volunteers ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quantification of extravascular fluid overload via ultrasound has rarely been studied in adults and never previously attempted in infants with CHD ( 26 , 35 ). Yanagisawa et al used ultrasound to evaluate for skin edema in pregnant women and was able to manually measure the depth of subcutaneous edema ( 26 ). A study by Eisenbeiss et al demonstrated that subcutaneous tissue thickness increased following fluid infusion and can be measured by ultrasound in healthy adult volunteers ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most utilized methods for assessing fluid overload include trending daily weights, net fluid balance, physical examination findings, and CVP measurements, all of which can be imprecise and can falsely represent a patient's fluid status due to the inherent inaccuracies in data collection and challenges distinguishing between intraand extra-vascular fluid overload (4,(15)(16)(17). Ultrasound, a fast and painless imaging modality that uses benign sound waves instead of ionizing radiation, has been studied in adults as a non-invasive measurement of fluid status by assessing the distensibility of vascular structures or extravascular fluid accumulation (18)(19)(20)(21)(22)(23)(24)(25)(26). MuscleSound, Inc., a Denver based ultrasound software company, has recently developed automated ultrasound measurements of skeletal muscle layers in the adult population that could be used to measure post-operative changes in subcutaneous edema and extravascular fluid overload (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Of these methods, only a physical examination may not be able to make a quantitative measurement of lymphedema. Ultrasonography, particularly portable ultrasonography, is easy to use and a very convenient tools for checking the degree of lymphedema [51]. Ultrasonography can easily detect increased skin thickness, increased subcutaneous tissue thickness, and increased subcutaneous echogenicity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that portable B-scan ultrasonography was able to quantitatively measure the increased thickness of the skin of the leg in pregnant women [51]. The skin thickness of the legs in pregnant women with edema was significantly increased compared with that in pregnant women without edema (6.4 ± 0.3 mm vs. 4.6 ± 0.4 mm) ( n = 98; p = 0.0001).…”
Section: The Diagnosismentioning
confidence: 99%
“…11,13 The skin’s thickness normally ranges between 0.5 to 3 mm, 8,14 but can be abnormally thick or thin when affected by disease processes. 5,15 Without this normalization step, skin stiffness estimates would be confounded by skin thickness at different anatomic locations, time points, and disease stages. Therefore, an accurate measurement of thickness is necessary to generate unbiased estimates of skin elasticity with ultrasonic SWE.…”
Section: Introductionmentioning
confidence: 99%